Association between advanced lung cancer inflammation index and distant metastasis in breast cancer: a retrospective cohort study - Luan, Xiao-dong; Ren, Qian; Zhang, Ya-lin; Zhang, Wen-hai; Liang, Chun-feng; Liang, Si-zhi; Liu, Zi-hao; Liu, Yu-kun (Frontiers in Oncology, 2025)
ObjectiveThis study aims to assess the relationship between the Advanced Lung Cancer Inflammation Index (ALI) and the risk of distant metastasis in breast cancer. While ALI is commonly used to evaluate the prognosis of lung cancer patients, its application in breast cancer and its correlation with distant metastasis are not well understood. Therefore, this study explores the potential of ALI as a predictor of distant metastasis in breast cancer patients.MethodsThis retrospective study included 348 breast cancer patients, of whom 163 had distant metastasis. Patient demographic information, tumor characteristics, and ALI values were collected. Multivariate regression analysis was used to adjust for confounding factors, and dose-response analysis was performed to investigate the relationship between ALI and the risk of distant metastasis. The optimal ALI cutoff value was determined, and its predictive performance was evaluated.ResultsThe analysis showed that patients with lower ALI had a significantly higher risk of distant metastasis. Adjusted multivariate analysis revealed that for every one interquartile range (IQR) increase in ALI, the risk of distant metastasis in breast cancer decreased by 31% (OR=0.69, 95% CI 0.58-0.81). Dose-response analysis indicated a linear relationship between ALI and metastasis risk. The optimal ALI cutoff value was identified as 36.39 using the Youden index, with an area under the ROC curve (AUC) of 0.605, indicating moderate predictive power of ALI for distant metastasis in breast cancer.ConclusionLower ALI is significantly associated with an increased risk of distant metastasis in breast cancer. ALI may serve as a valuable predictor of distant metastasis, offering clinicians a new tool to better identify high-risk patients and facilitate early intervention. However, further prospective studies are required to validate its clinical utility.